Culture-specific Writing Styles in Postgraduate Students’ Research Proposals - Olga Boginskaya (Forma y Función)
Academic communication occurs in a multicultural world with different culture-specific academic writing standards, intellectual styles and discourse expectations. Yet despite these differences, globalization of scholarship has considerably levelled out the standards on academic writing. The study aims to explore the impact of intellectual styles on choosing metadiscourse resources by non-native English writers from different cultural backgrounds in the context of globalized higher education. The participants were 116 engineering students who were taking a postgraduate course. To investigate hedges and boosters in students’ research proposals, the methods of quantitative and contextual analysis were adopted. Research proposals by Asian and East European postgraduate students were taken for the cross-cultural study based on Galtung’s and Hind’s theories of writing styles. Findings revealed that research proposals by Slavic students exposed to Teutonic writer-responsible culture featured a larger number of hedges. Asian-authored writing that is considered to be influenced by Nipponic reader-responsible culture and often regarded as indirect featured far more boosters than Slavic-authored texts considered to be precise and clear.